The implications of the Corona pandemic on the application of accounting assumptions, principles, and determinants: theoretical research (Economic studies journal, 2021)
AbstractThis research focuses on the economic and social implications of the Corona pandemic on the implementation of the Accounting assumptions, principles, and determinations, based on the Documentary Approach, which require Collects the data from the publications of the international accounting organizations, international accounting, and Auditing firms to analyze the opinions and instructions by thematic analysis. The importance of the research lies in the novelty of the topic. The conclusion of this study includes several results, the most important of which are: many financial and economic indicators show up because of the pandemic, these indicators may cast doubt on applications of the continuity assumption, which may hurt unity assumption, accounting principles, and determinations. Besides, the measurement principle faces difficulties on applying according to the lack of reliable measurement inputs which excess the accountants using the personal estimates, especially when using the fair value. Moreover, the pandemic requires a reconsideration of the applying of the principle of expense recognition, the principle of revenue recognition, and accounting recognition policies for these principles. The need for more disclosure of information increases especially those related to future risks and possibilities according to the pandemic. Furthermore, the accountant needs to reconsider the cost-benefit analysis when producing accounting information and the practice that concerns conservatism. According to these results, several recommendations propose to assist the accountants and the stakeholders during and after the pandemic.
Keywords: Accounting, Accounting assumptions, Accounting determinations; Accounting principles; Corona pandemic.